A sliding mode speed and position observer for a surface-mounted PMSM. (April 2019) - Chen, Yong; Li, Meng; Gao, Yu-wen; Chen, Zhang-yong
Abstract: To improve the speed and position observation performance of a Surface-Mounted Permanent Magnet Synchronous Motor (SM-PMSM), an improved sliding mode observer (SMO) based on the adaptive synchronization filter (ASF) and quadrature phase-lock loop (QPLL) is proposed. An adaptive synchronous filter based on feedback rotor position estimation from a QPLL is proposed to extract the fundamental signal of the back electromotive force (back-EMF). Then, a QPLL is linked to calculate the rotor position and speed according to the fundamental signal of the back-EMF, in order to effectively suppress the estimated harmonics and chattering and improve the observation accuracy of speed and position. Finally, the effectiveness and feasibility of the proposed observer approach are verified by simulation and dSPACE. Highlights: An improved sliding mode observer (SMO) based on the adaptive synchronization filter (ASF) and quadrature phase-lock loop (QPLL) is proposed. An adaptive synchronous filter based on feedback rotor position estimation from a QPLL is proposed to extract the fundamental signal of the back electromotive force (back-EMF). A QPLL is linked to calculate the rotor position and speed according to the fundamental signal of the back-EMF, in order to effectively suppress the estimated harmonics and chattering and improve the observation accuracy of speed and position.